Agatha Christie Queen of Crime - Christie, Agatha 1890-1976; Christie, Agatha 1890-1976 (Great Movies GmbH, 2021)
The wife of a Foreign Office diplomat discovers a body in the drawing-room of her house in Kent. [imdb.de]